Analgesia preemptiva com cloridrato de tramadol em ovariohisterectomia de cadelas - Schneider, Luciana (2018)
Post-operative pain is one of the main complications and its control is essential to increase well-being and facilitate patient recovery. One of the most effective means of pain control is preemptive analgesia and the most commonly used analgesic is tramadol hydrochloride. The aim of this study was to evaluate the preemptive effect of tramadol hydrochloride at a dose of 6 mg / kg. For that, 29 female dogs with no defined breed, of different ages and average weight of 10 kg were selected, which were submitted to elective ovariohysterectomy. Randomly distributed into three groups, the first group (CT-MPA) received tramadol hydrochloride only on preanesthetic medication (MPA), the second group (CT-6) received one dose of the drug 6 hours before MPA and the third group (CT-24) every 6 hours, for 24 hours before MPA. Postoperative pain assessment was performed with the Glasgow Scales and Visual Analogue Scale (EVA) by two observers at one hour intervals, starting one hour after the animal extubation. For salvage analgesia, 6 mg / kg of intramuscular tramadol and 1 mg / kg of ketoprofen were used subcutaneously, six hours after extubation or when EVA reached 33%, indicating pain. The CT-6 and CT-24 groups had the lowest pain rates, presenting a greater analgesic effect due to repeated administration. However, at the end of the evaluation, the CT-24 group remained constant, with no decrease in pain indexes, because repeated administration of tramadol led to the development of tolerance of its effect, and the CT-6 group received only one dose before of MPA had its effect enhanced. With this, it was concluded that the use of tramadol hydrochloride preemptively with only one dose prior to pre-anesthetic medication results in a greater analgesic effect in the immediate postoperative period.